The Impact of the Implementations of the SysTrust's Framework upon the Quality of Financial Reporting: Structural Equation Modelling Approach - Ahmad Al-Dmour; Maysem Abbod; Rand H. Al-Dmour (Journal of Accounting and Management Information Systems (JAMIS), 2018)
The purpose of this research is to examine empirically, validate, and predict the reliability of the proposed relationship between the reliability of AIS process in the context of SysTrust' framework (principles and criteria) and the quality of financial reporting in shareholdings companies in Jordan. For this purpose, a primary data was used that was collected through a self-structured questionnaire from 239 of shareholdings companies. The extent of SysTrust's framework (principles and criteria) and the quality of financial reporting were also measured. The data were analyzed using structural equation modeling. The results showed that the magnitude and significance of the loading estimate and they indicated that all of the main five principles of SysTrust's framework are relevant in predicting the quality of financial reporting. Moreover, the reliability of AIS by the implementation of these five principles of SysTrust's framework were positively impacting the quality of financial reporting, as the structural coefficient for these paths are significant.
Keywords: M41; 650; SysTrust principles; internal control System; AIS; Jordan; shareholdings companies